2022
DOI: 10.52312/jdrs.2022.550
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital complications following total knee and hip arthroplasty in patients with human immunodeficiency virus

Abstract: Total joint arthroplasty (TJA) is a treatment option that has been increasingly preferred in conditions which lead to joint damage such as severe osteoarthritis (OA), rheumatoid arthritis or avascular necrosis (AVN). [1][2][3] Patients with conditions that particularly affect the hip and knee joint experience a considerably impaired quality of life (QoL), [4][5][6] in which two main TJAs, i.e., total hip arthroplasty (THA) and total knee arthroplasty (TKA) are frequently preferred in the treatment of such pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Akkaya et al. [ 20 ] included 11 HIV-positive patients undergoing unilateral TKA and found that 2 patients experienced complications, with one encountering deep vein thrombosis and the other developing acute renal failure. However, the authors of this review concluded that the increased complication rate of this study in comparison to existing literature was attributed to the elevated age of their cohort (60.8 ± 16 years) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Akkaya et al. [ 20 ] included 11 HIV-positive patients undergoing unilateral TKA and found that 2 patients experienced complications, with one encountering deep vein thrombosis and the other developing acute renal failure. However, the authors of this review concluded that the increased complication rate of this study in comparison to existing literature was attributed to the elevated age of their cohort (60.8 ± 16 years) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…No reports of deep periprosthetic infection. Mean preoperative KSS objective score: HIV+:41, HIV−:42 P = .31; Mean preoperative KSS functional score: HIV+:45, HIV−:44 P = .33; Mean postoperative KSS objective score: HIV+:89, HIV−:91 P = .38; Mean postoperative KSS functional score: HIV+:88, HIV−:90 P = .36; Mean preoperative UCLA score: HIV+: 4 HIV−: 4, P = .63; Mean postoperative UCLA score: HIV+: 6 HIV−: 6, P = .54 Akkaya et al., 2022 [ 20 ] IV 11 HIV+ patients To assess complication rate for HIV+ patients undergoing TKA Not reported 2 patients (18.2%) developed complications such as deep vein thrombosis and acute renal failure. Not reported Not reported Lin et al., 2014 [ 21 ] IV 4 HIV+ and 239 HIV− patients Assess outcomes for HIV+ and HIV− patients undergoing TKA No significant difference in Kaplan-Meier survivorship curve between HIV+ and HIV−patients; No significant difference in number of revisions between HIV+ and HIV− patients.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the incidence of acute renal failure was higher in the HIV/AIDS group compared to the group without HIV/AIDS. In a retrospective cohort study of, Akkaya et al reported 1 patient out of 11 HIV positive TKA patients developing acute renal failure [ 9 ]. A study by Lin et al has reported the rate of kidney failure in joint replacement patients with HIV/AIDS a higher incidence of acute renal failure in HIV/AIDS patients (4.2%) who underwent joint replacement than in HIV-negative patients (1.6%) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Joint arthroplasties are the procedure of choice that have been increasingly adopted in conditions leading to joint damage, such as severe osteoarthritis (OA), rheumatoid arthritis, and avascular necrosis. [ 1 - 3 ]…”
mentioning
confidence: 99%
“…
Joint arthroplasties are the procedure of choice that have been increasingly adopted in conditions leading to joint damage, such as severe osteoarthritis (OA), rheumatoid arthritis, and avascular necrosis. [1][2][3] Patellar resurfacing is optional during total knee replacement (TKR). Some surgeons always resurface the patella and some never resurface, while others selectively resurface.
…”
mentioning
confidence: 99%